Dzieje parafii unickiej pw. św. Michała w Łosińcu do 1875 roku - FRYKOWSKI, Janusz Adam (Historia i Świat, 2015)
The introduction of the article contains the parish geographical location, its size and the place within the Church hierarchical structure. Having analyzed post- visit inspection protocols by Chelm Bishops as well as statistical specifications the look, fittings and ancillary equipment of the parish church and its affiliated churches was recounted. As far as possible the look of vicarage and ancillary buildings was introduced as well. Not only was the list of 19 clergy recreated but also the Orthodox church benefice was defined. The other part render the number of worshipers as well as the number of Holy Communion receivers.